APPROACHES TO ENHANCING OPENNESS AND TRANSPARENCY IN CITIES: THE BARCELONA EXPERIENCE - Zhylinska L.О. (SWorld-Ger Conference proceedings, 2023)
This article explores approaches to increasing openness and transparency in cities, using Barcelona as a shining example. It underscores Barcelona as a city actively working to enhance transparency and community engagement in urban governance. It is demon